Fluorescent, Plasmonic, and Radiotherapeutic Properties of the 177Lu–Dendrimer-AuNP–Folate–Bombesin Nanoprobe Located Inside Cancer Cells. (3rd May 2017) - Mendoza-Nava, Héctor; Ferro-Flores, Guillermina; Ramírez, Flor de María; Ocampo-García, Blanca; Santos-Cuevas, Clara; Azorín-Vega, Erika; Jiménez-Mancilla, Nallely; Luna-Gutiérrez, Myrna; Isaac-Olivé, Keila
The integration of fluorescence and plasmonic properties into one molecule is of importance in developing multifunctional imaging and therapy nanoprobes. The aim of this research was to evaluate the fluorescent properties and the plasmonic–photothermal, therapeutic, and radiotherapeutic potential of 177 Lu–dendrimer conjugated to folate and bombesin with gold nanoparticles in the dendritic cavity ( 177 Lu–DenAuNP–folate–bombesin) when it is internalized in T47D breast cancer cells. The intense near-Infrared (NIR) fluorescence emitted at 825 nm from the conjugate inside cells corroborated the usefulness of DenAuNP–folate–bombesin for optical imaging. After laser irradiation, the presence of the nanosystem in cells caused a significant increase in the temperature of the medium (46.8°C, compared to 39.1°C without DenAuNP–folate–bombesin, P < 0.05), resulting in a significant decrease in cell viability (down to 16.51% ± 1.52%) due to the 177 Lu–DenAuNP–folate–bombesin plasmonic properties. After treatment with 177 Lu–DenAuNP–folate–bombesin, the T47D cell viability decreased 90% because of the radiation-absorbed dose (63.16 ± 4.20 Gy) delivered inside the cells. The 177 Lu–DenAuNP–folate–bombesin nanoprobe internalized in cancer cells exhibited properties suitable for optical imaging, plasmonic–photothermal therapy, and targeted radiotherapy.